Spontaneous Pneumothorax as Clinical Presentation in a Patient with COVID-19 - Devkota, S.; Shrestha, S. (Kathmandu University Medical Journal, 2022)
Spontaneous pneumothorax as an initial presentation is very rare in COVID-19 patient. We present a case where the initial presentation was that of a mild disease and on investigation was found to have pneumothorax without any predisposing risk factors.